Management of Primary Lymph Nodal Gastrinoma With Liver Metastases Resulting in Zollinger-Ellison Syndrome. (January 2019) - Singh, Deepa; Lal, Sadhna B.; Sood, Ashwani; Gupta, Rajesh; Kumar, Rajender; Vashishta, Rakesh K.; Mittal, Bhagwant Rai
Abstract : Abstract: Primary lymph node gastrinoma has been defined as gastrin-producing tumor present in lymph nodes and predominantly found in well-defined anatomical region known as gastrinoma triangle. They are usually localized preoperatively with imaging, and their surgical resection results in long-term relief. The authors report a case of unresectable primary lymph nodal gastrinoma with liver metastases in a 14-year-old adolescent boy with proven histopathology detected on 68 Ga-DOTANOC whole-body PET/CT scan followed by preoperative multiple 177 Lu-DOTATATE cycles for cytoreduction. Subsequent surgical resection of residual mass resulted in complete response with a follow-up of around 4 years in this unusual case of Zollinger-Ellison syndrome.